Under-ice environment observations from a remotely operated vehicle during the MOSAiC expedition - Philipp Anhaus; Christian Katlein; Stefanie Arndt; Daniela Krampe; Benjamin A. Lange; Ilkka Matero; Evgenii Salganik; Marcel Nicolaus (Scientific Data)
Abstract Changes in the Arctic sea-ice cover affect the planet’s energy budget, atmospheric and oceanic circulation patterns as well as the ecosystem associated with this unique habitat. Interdisciplinary observations at the interfaces between sea ice and ocean are crucial to better understand the driving processes and bio-physical linkages in this coupled system. During the MOSAiC expedition 2019/2020 to the Arctic Ocean, we used a remotely operated vehicle (ROV) underneath drifting sea ice throughout an entire year. The main objective was to measure physical, chemical, and biological parameters across different surface and sea-ice types while the dive missions were optimized to retrieve optical properties and sea-ice bottom topography. All parameters were measured synchronously, enabling the quantification of their relationships and spatial and temporal variability. In addition, visual documentation of the under-ice environment and the permanently on-ice deployed instrumentation was performed. Overall, we completed more than 80 surveys covering all seasons and various sea-ice and surface conditions. Here, we present all available data, allowing for a year-round comprehensive picture of the under-ice environment.